Transcultural adaptation of Kidcope to portuguese (Brazil) - Guerra Pereira, Hedyanne (2016)
The objective of this paper was to translate and carry out the cross-cultural adaptation of Kidcope´s instrument to Portuguese (Brazil). The conceptual and item equivalence, semantic and operational equivalence between the original instrument and the Brazilian version of the Kidcope were performed in this cross-sectional methodological research. The results show a good conceptual and item equivalence, besides semantics between the elements of the original instrument and the translations, especially with reference to the T2 - R2 dyad. Regarding operational equivalence, the children confirmed to instrument as adequate and comprehensible. The study reached the desired goal and the results were satisfactory, noting the possibility of continuing to the next stage, the equivalence of measurement.